PERILAKU PEMEGANG SAHAM PREFERENSI KONVERTIBEL EMAS DALAM MENGHADAPI INITIAL PUBLIK OFFERING - Susilowati Rahayu (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
The purpose of this study is to investigate the behavior of holders of Convertible Preferred Stocks Gold (CPS-GOLD) after the company decided to go public. The results of ten respondents indicated that information obtained from the CPS-GOLD friends. 80% of shareholders to get their capital from bank loans. 20% of shareholders' equity to subscribe using CPS-GOLD. 60% shareholder seeking other revenue to pay off the debt to the Bank. 80% have a turnover of shareholders and immediately sell the shares and does not convert into common stock.